Henry the Green Engine : Toby the Tram Engine : Gordon the Big Engine - Awdry, Rev. W.; Illustrated by Dalby, C. Reginald (England Marks and Spencer, 1984)
This is a story about Henry the Green Engine. Henry was often ill and couldn't work. But then he tried some special Welsh coal, and got the chance to show everyone just what he could do...
Include Colour Illustrations
Keywords: Children's stories, English -- Steam-engines